Kommunalt självstyre i energiomställningen: En jämförande studie av stigberoende, icke-beslutsfattande och lokala energipolitik i Laholm och Båstad - Strömberg,Maximilian; Wållgren Olsson,Elias (2026)
The Swedish energy transition presupposes a large-scale expansion of renewable electricity generation, in which wind power constitutes a central component. At the same time, the expansion of wind power exhibits significant local variation. This thesis analyses how physical conditions interact with municipal institutions and long-term policy processes in shaping local wind power policy, with a focus on the differences between the municipalities of Båstad and Laholm. The study is conducted as a qualitative comparative case study based on text analysis of municipal policy documents, planning materials, consultation responses, and supplementary media sources from the period 2000–2025. The theoretical framework combines implementation theory and power theory by employing path dependency as a central analytical concept. The analysis is further complemented by the phenomena of NIMBY and the municipal veto, which illuminate specific obstacles to implementation and expressions of local power. The analysis shows that Laholm, due to larger contiguous areas with less hostility from housing and tourism, has had more favourable physical conditions for large-scale onshore wind power than Båstad. At the same time, the study demonstrates that the differing outcomes can largely be understood as the result of path-dependent policy trajectories, in which early decisions, conflicts, and planning choices have gradually become institutionalised and constrained later room for manoeuvre. In Laholm, this has enabled a selective integration of wind power, while Båstad has developed a stable restrictive policy trajectory. The study thus highlights how municipal self-government, in interaction with geography and institutional inertia, shapes the implementation of national energy policy.
Keywords: Vindkraftsutbyggnad; Laholm kommun; Båstad kommun; Lokalt motstånd; Stigberoende